OPTIMALISASI TEKANAN SHOCK ABSORBER DAN TEKANAN PEGAS COIL TERHADAP GETARAN MOBIL - listiyono yono listiyono; Nurhadi Nurhadi; Agus Hardjito (Jurnal Energi dan Teknologi Manufaktur, 2020)
Safety and comfort are the valuable factor for the driver. One of the safety factor refers to the steering accuracy. Steering wheel hardness must be soft when turning but remain stable in straight track. The comfort factor refers to the bouncing effect when the car passing in rough track. Those two factors is depend on the shock absorber components. This study aims to know the optimum gas pressure and spring pressure to obtain the maximum vibration reduction. This study use the experimental methods use the 6 bar, 8 bar, and 10 bar of absorber pressure. The spring pressure used in this study is 20 , 25 dan 30 (Kg/cm2). The data obtained were analyzed with MINITAB software. From the results of research on Optimizing Shock Absorber Pressure and Coil Spring Pressure Against Car Vibrations can be concluded as follows: 1. There is an influence of absorber pressure and spring pressure on the suspension on the amount of vehicle vibration. The optimum absorber pressure is 10 (bar). 2. The optimum coil spring pressure at 24 (kg / cm2).